2021
DOI: 10.3390/jcm10204629
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Different Reperfusion Strategies of Multivessel Disease Undergoing Newer-Generation Drug-Eluting Stent Implantation in Patients with Non-ST-Elevation Myocardial Infarction and Chronic Kidney Disease

Abstract: Because available data are limited, we compared the 2-year clinical outcomes among different reperfusion strategies (culprit-only percutaneous coronary intervention (C-PCI), multivessel PCI (M-PCI), complete revascularization (CR) and incomplete revascularization (IR)) of multivessel disease (MVD) undergoing newer-generation drug-eluting stent implantation in patients with non-ST-elevation myocardial infarction (NSTEMI) and chronic kidney disease (CKD). In this nonrandomized, multicenter, retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(63 reference statements)
0
2
1
Order By: Relevance
“…Due to comorbid conditions and increased periprocedural events, managing the multivessel lesions in patients with CKD is more complicated. 10 In contrast to a prior Korean retrospective cohort study that found MV-PCI failed to reduce death during a 24-month follow-up period, 22 our results supported the use of MV-PCI among UA/NSTEMI and CKD. The inconsistency could likely be attributed to heterogeneities in the patients enrolled and study methods.…”
Section: Discussioncontrasting
confidence: 65%
“…Due to comorbid conditions and increased periprocedural events, managing the multivessel lesions in patients with CKD is more complicated. 10 In contrast to a prior Korean retrospective cohort study that found MV-PCI failed to reduce death during a 24-month follow-up period, 22 our results supported the use of MV-PCI among UA/NSTEMI and CKD. The inconsistency could likely be attributed to heterogeneities in the patients enrolled and study methods.…”
Section: Discussioncontrasting
confidence: 65%
“…In a recent publication [ 35 ], consistent with previous reports [ 33 , 34 ], the 2-year major clinical outcomes were similar between the early invasive and delayed invasive groups in patients with NSTEMI (n = 8241) in the four different renal function groups. Kim et al [ 37 ] also suggested that culprit-only PCI may be a better reperfusion option for patients with NSTEMI with multivessel disease and CKD rather than multivessel PCI, including complete revascularization and incomplete revascularization, with regard to the procedure time and the risk of contrast-induced nephropathy. In our study, as shown in Supplementary Table S2 , STD (< 24 h vs. ≥ 24 h) was not an independent predictor of MACCE, all-cause death, CD, and non-CD in both the CKD and non-CKD groups.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers on percutaneous coronary intervention (PCI) were published in Korea and Japan. Kim et al [ 4 ] revealed that differences in reperfusion strategies did not significantly affect prognosis in patients with multivessel non-ST-elevation myocardial infarction and chronic kidney disease, emphasizing the need for further investigation of the optimal perfusion strategy. Noma et al [ 5 ] reported that adjunctive catheter-derived thrombolysis with intracoronary monteplase delivery resulted in favorable outcomes in patients with ST-elevation myocardial infarction, especially in those with a high thrombus burden who were refractory to primary PCI procedures.…”
mentioning
confidence: 99%